Present Status of the Effectiveness of the Patch Test Reagent for Titanium Hypersensitivity - Koike, Mari; Susan, Hummel; Hiraba, Haruto; Shimoe, Saiji (The Journal of Dentists, 2023)
Titanium and titanium alloys have been used for dental implants, due to their excellent biocompatibility and suitable mechanical properties. The frequency in use of titanium and titanium alloys for dental applications has gradually increased. For example, in 2020, a Japanese insurance approved the use of pure titanium for posterior molars as a metallic cast crown. Titanium alloys have also been used for frameworks of removable partial denture. Allergic reactions to titanium and titanium alloys are rare but do occur. One theory of unexplained implant loss is that the patient is hypersensitive to titanium. The hypersensitivity causes an inflammatory reaction to the implant body and failure to osseointegrate, resulting in implant failure. The patch test for diagnosis of titanium hypersensitivity has been unreliable because the result of the patch test does not match the clinical symptoms. Standard titanium reagents for patch tests are needed for accurate diagnosis of titanium hypersensitivity to prevent the failure of implants. The objective of this review was to evaluate literature reporting the status of allergic diagnosis for titanium hypersensitivity and analyze the results mentioned. Based on these results, a possible standardization of the titanium reagent for the patch test were discussed. These searched literatures indicated that further national and/or registry based studies will be needed to better inform clinical practice and to identify the scale of metal sensitivity, clear diagnostic criteria, and long-term clinical performance data on hypoallergenic implants.